Diagnostic utility of semen analysis in infertile couples: a prospective study - Jandial, Roopali; Choudhary, Mehnaz; Singh, Kuldeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is defined as a failure to conceive after at least 12 months of unprotected intercourse. It is broadly established that 40% cases of infertility has male factor. Semen analyses is an imperative diagnostic tool in the valuation of the male partners of infertile couples. Methods: We carried out a prospective study wherein semen analyses of the male partners of infertile couples presented to Department of Pathology, Government Medical College and Associate Hospital, Jammu was done. A total of 300 cases were studied and comparison of each abnormality and combined defects were subjected to incidence distribution. Results: We analysed 300 samples in this study. Mean age of the men was 32.5 years. Duration of infertility in (200; 66.6%) was seen in men married for less than 5 years, (84; 28%) between 5-10 years of married life and there were (16; 5.3%) with more than 10 years of infertility period after marriage. Addiction to alcohol made the majority in our study (187; 62.3%), followed by tobacco chewing and addiction to both tobacco chewing and alcohol consumption (89; 29.6%) and (24; 8%), respectively, men were amongst those with abnormal seminograms. Conclusions: Male infertility is an alarming global health issue. Males contribute towards infertility in couples significantly and further study and assessment is required to accurately predict the importance of this.